Kenampakan Pedologi Tanah Sawah yang Berasal dari Toposekuen Berbahan Induk Volkanik di Daerah Bogor – Jakarta - Teti Arabia; Sarwono Hardjowigeno; Sudarsono Sudarsono; Widiatmaka Widiatmaka; Nata Suharta (Jurnal Agrista, 2009)
(The Pedological Features of Paddy Soils from a Toposequence on Volcanic Parent Materials in the Bogor – Jakarta Area)ABSTRACT. The pedological feature of paddy soils are different from the non paddy cultivated. The aim of the research were: to study the pedofeatures of paddy soils in a toposequence on volcanic materials in the Bogor – Jakarta area; to study the influence of paddy cultivated intensity of pedofeatures. Twelve pedons of different altitude (90 – 650 m above see level) and different paddy cultivated intensity (0/year, 1/year, 2/year) were investigated, each horizons were sampled for laboratory analysis to study the pedofeatures. The result of the research showed that on non paddy cultivated, pedofeature observed at B horizon is indicating rock weathering. On 1x paddy, at tillage layer nodules and hypocoating were found. On 2x paddy, at plow plan layer clay infilling dense complete was found.